Different outlet for preparing nano-TiO2 catalysts for the photodegradation of Black B dye in water - Ahmed K. Aboul-Gheit; Doaa S. El-Desouki; Radwa A. El-Salamony (Egyptian Journal of Petroleum)
Two nano-titania catalysts were prepared using two economically varying titanium precursors: titanium tetrachloride (A) and titanium isopropoxide (B). The catalysts were calcined at temperatures of 500 °C, 600 °C and 700 °C and characterized using X-ray diffraction (XRD), electron diffraction (ED), BET surface properties and high resolution transmission microscopy (HRTEM). The calcined catalysts were found to differ markedly in their physical characters and TiO2 phases produced as well as their photocatalytic activities. The anatase titania phase diminished from 100% to 83% in TiO2A but from 64% to zero in TiO2B via temperature increase from 500 °C to 700 °C, due to transforming anatase to rutile. The brookite TiO2 phase only appeared (17%) in catalyst B500. In general, the catalyst of choice is A600 by virtue of many compositional, economical and catalytic advantages.